QR Code Based Scrapbook Learning Media to Improve Class IV Student Learning Outcomes - Mahendra, Dewa Gede Rai; Agustiana, I Gusti Ayu Tri (Universitas Pendidikan Ganesha, 2024)
Low student learning motivation results in low learning outcomes. This is caused by teachers not utilizing learning media that can encourage student participation. Based on this, research was carried out which aimed to analyze the effectiveness of QR code-based scrapbook learning media to improve the learning outcomes of class IV students. The subjects of this research were 28 class IV students. The development model used is the ADDIE model. Data collection methods are observation, interviews, questionnaires, and test methods. Data collection instruments are assessment scales, assessment sheets, and test sheets. Data analysis techniques use qualitative and quantitative analysis. The results of the media feasibility test received a very decent qualification. Testing the effectiveness of the media obtained the results that H0 was rejected and H1 was accepted, so it can be concluded that the QR code-based scrapbook media is effectively used to improve the learning outcomes of class IV students. The implication of this research is that it can be used as a reference for teachers in presenting learning media that is interesting and appropriate to student characteristics.